IMPLEMENTASI PENDIDIKAN INKLUSI DI KOTA KEDIRI: STUDI KASUS DI SMP YBPK KEDIRI - Fathimatul Zahrol F, Ninik Zuroidah dan (IAIN Kediri, 2015)
In order to pursue educational equity for Indonesian citizens , the government has issued a policy on inclusiveÃ‚Â educational programs in schools. The programs aim to provide for all children, including those with specialÃ‚Â needs. Schools that implement inclusive education should accommodate the students with special needs in termsÃ‚Â of curriculum, teachers, lesson facilities, and learning activities. Based on a field research, this article examinesÃ‚Â the implementation of inclusive education in YBPK Junior High School Kediri, which is the first inclusive JuniorÃ‚Â High School in Kediri where most of students require special needs. This study revealed that through approriateÃ‚Â plans and adjustment in materials and methods, the teachers are succesfull in increasing socialization of theÃ‚Â students with special needs in the school.Keywords: Pendidikan Inklusi, SMP YBPK Kediri, Anak Berkebutuhan Khusus (ABK)